Case Report: Congenital disseminated tuberculosis neonate born to tuberculosis- COVID-19 mother - Risan, Nelly Amalia; Febrianda, Rilda Dwi; Nataprawira, Heda Melinda (Frontiers in Pediatrics, 2022)
We report a case of a 26-days-old male neonate with high suggestive of congenital disseminated tuberculosis (TB) (tuberculous meningitis (TBM), pulmonary TB, and ocular TB) at term, low birth weight born cesarean section from a confirmed COVID-19 and pulmonary TB mother who hospitalized in the isolation room and never seen her son for three weeks. The baby had fever since two weeks after birth and with a history of seizures. Nasopharyngeal swab for RT-PCR SARS-CoV-2 yielded a negative result. He was initially diagnosed as having sepsis-like syndrome and then hospitalized. Chest X-ray revealed bilateral infiltrate, cerebrospinal fluid analysis (CSF) showed clear, cell count was 9 with dominant mononuclear cell, and gastric lavages did not yield acid-fast bacilli. X-pert MTB/RIF from gastric lavage specimen detected Mycobacterium tuberculosis rifampicin sensitive. Anti-tuberculosis drugs for TBM were started. Abdominal sonography identified multiple hypoechoic nodules in the liver and spleen. Neuroimaging studies did not identify hydrocephalus, meningeal enhancement, infarct, or tuberculoma. Video-EEG examination showed electrical seizure after initiation of phenobarbital. Video-EEG evaluation showed no epileptiform discharge. Upon follow-up, he showed slightly delay motor development, pan-uveitis, retinal detachment, and cataract. We assumed that ocular TB resulting as paradoxical reaction following TB treatment. Retinal detachment was improved and lens replacement was done.